Increase of muscle during strenuous exercise can have negative consequences - Самойлов [Nikolay Samoilov], Микола Григорович (Slobozhanskyi Herald of Science and Sport, 2013)
The aim was to study the changes that occur in tetanus as a result their hypertrophy. The experiment was performed on laboratory white rats that received strenuous exercise by running in a treadmill. Found that, depending on the intensity and duration of the running in the muscles change the ratio of hypertrophy and hyperplasia processes. Small and average speed and intensity of strenuous exercise causes an increase of ultimate size at the cost of fascicular degradation formed by increasing the number of fain-grains – myofibrils. Great intensity and running speed also increase to the height of ultimate size namely to the hypertrophy, but this process is accompanied by a significant development deleterious, destructive changes in the hypertrophied muscles. Therefore, the use of strenuous exercise as a factor by which you want to achieve increased muscle, you should remember that the large height of strenuous exercise lead to activation of collapsing fine-grains in hypertrophied muscles.